Zoledronic acid overdose in a two-year-old with osteogenesis imperfecta - Brandtly Yakey; Mirjana Dimovska; Bram Dolcourt; Varun Vohra (Toxicology Communications, 2023)
AbstractZoledronic acid is an intravenous (IV) bisphosphonate used to treat bone metastases associated with solid tumors and metabolic bone disorders. It is an established treatment option for children with osteogenesis imperfect (OI). Its efficacy relies on its higher potency and affinity for bone, shorter infusion time, and long-acting kinetics. While therapeutic safety and efficacy have been established, zoledronic acid overdose has been rarely reported. We present a case of a 15-fold zoledronic acid overdose in a 2-year-old child treated for OI requiring pediatric intensive care unit admission. The patient developed hypocalcemia and hypophosphatemia requiring repletion along with ergocalciferol supplementation. He also developed a transient acute phase reaction and electrocardiogram disturbances and underwent hemodialysis. He was discharged on hospital day 12. Zoledronic acid has been associated with electrolyte abnormalities, nephrotoxicity, acute inflammatory responses, metabolic derangements, and arrhythmias. A lack of zoledronic acid concentrations limited our ability to characterize a toxicokinetic profile and precluded an interpretation of the relationship between serum concentrations and clinical effects. Limited clinical experience and literature were available to guide the management of this overdose. Management approach principles should be based on aggressive electrolyte monitoring and supplementation, renal function and cardiac monitoring, and pre-and post-morbid assessment of metabolic parameters.